ANTON CHEKHOV'S STORY «HOUSE WITH A MEZZANINE» IN THE LITERARY-CRITICAL INTERPRETATION OF YA. V. ABRAMOV: REPRESENTATION OF IDEAS OF SOCIAL EVOLUTIONISM - V. M. Golovko (Гуманитарные и юридические исследования)
Review article «Small and great things» by an outstanding social and literary figure of the era of «the second going to the people», one of the ideologists of «cultural» course in legal populism of 1880s-1890s, Ya. V. Abramov (1858-1906), which is dedicated to Anton Chekhov's story «House with a mezzanine», has not yet attracted the attention of researchers, although it represents methodologically sound and scientifically credible interpretation of the moral and aesthetic position of the author, embodied in this work. Genre synthesis of literary criticism and journalistic principles, characteristic of the article by Y. Abramov, is due to the desire of the reviewer to represent the peaceful program of gradual progress of Russia in the name of the liberation of the people from the material needs and spiritual enlightenment. The essence of the program, the contents of which can not be labeled with the term «abramovschina», is revealed during the analysis of the dialogical nature of the artistic interpretation of the author of «House with a mezzanine», the theory and practice of «small deeds». Occupying a special position in the reformist populism and actualizing the idea of democratic enlightenment, Ya. V. Abramov sees «modest activity» of supporters of the «small deeds» not as universal means of social and cultural progress, but as historically determined form of socially useful activity. It is, as shown in the «Small and great things» article, associated with the implementation of the main goals of «great cultural work» and aims to change the entire «order of life», to achieve the ideals of humanism, individual liberty and social justice. As the phenomenon of intellectual history, the ideological legacy of Y. Abramov, a thinker and writer, is particularly relevant in today's Russia.